(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
The aim of the research was to find out the possibilities for reducing the prime cost of environmentally safe technologies fo the preparation of herbaceous fodder by improving technical means. During the recent years, on major individual and co? operative farms there is being introduced a perspective roll technology of processing wilted green grass with subsequent sealing of rolls m a flexible film. The advantages of the green grass processing technology with subsequent sealing of rolls in a flexible film are: - environmental safety o f the technology (exclusion of pollution with silo saps, absence o f odour nuisance, absence o f compounds m the feed that are detrimental to animals and formed during the common siloing, its low acidity); - considerably lower dependence of forage processing on weather conditions, complete mechanisation of engineering processes; - the forage can be processed in small quantities, and for its storage no specialised containers are needed, which is a valuable feature for small farms; - increased nutritive value and good gustative qualities providing a possibility of essential raising the yields of milk and its quality (retention of all nutrients and vitamins), insignificant losses of nutrients during the harvesting and storage period (not more than 10-15%).